Implementation of Disaster Mitigation Educational Policies in Pre-school: A Case Study of Effective Steps in Preparing Children for Disaster - Samad, Munawwarah; Fitriani, Dewi; Wahyuni, Sri; Yacob, Fakhri; Fahrizqa, Nursarirati (Department of Government Studies, Universitas Syiah Kuala, 2024)
Disaster mitigation for early childhood involves introducing preparedness before and after a disaster to reduce vulnerability risks. The objective of this study is to examine the implementation of disaster education policies in early childhood education. This descriptive qualitative research employs interviews, observation, and documentation as data collection techniques. The research subjects include two teachers and the principal at PAUD IT Insan Madani Meukek, South Aceh. The findings indicate that the implementation of disaster mitigation education policies in early childhood education has been effectively operationalized, such consistent integration of disaster preparedness into curriculum activities and adequate training and support provided to educators. furthermore, the teachers role is critical as a planner, organizer, implementer, communicator, director, and facilitator in disaster mitigation education for early childhood. Additionally, according to Van Meter and Van Horn's policy implementation theory, the effectiveness of implementing disaster mitigation education in preschools is influenced by the clarity of policy objectives, availability of resources, inter-organizational communication, as well as the attitudes of the implementers.